1996
DOI: 10.1161/01.res.78.2.262
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Mechanism of Action Potential Prolongation in Ventricular Myocytes From Dogs With Pacing-Induced Heart Failure

Abstract: Membrane current abnormalities have been described in human heart failure. To determine whether similar current changes are observed in a large animal model of heart failure, we studied dogs with pacing-induced cardiomyopathy. Myocytes isolated from the midmyocardium of 13 dogs with heart failure induced by 3 to 4 weeks of rapid ventricular pacing and from 16 nonpaced control dogs did not differ in cell surface area or resting membrane potential. Nevertheless, action potential duration (APD) was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
274
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 496 publications
(297 citation statements)
references
References 38 publications
19
274
4
Order By: Relevance
“…Our electrophysiological data support the possibility that similar alterations occur in the STZ‐hyperglycemic mouse model employed here. Importantly, reduction in the outward K + Kv currents and prolongation of AP duration in mammals appear to be a conserved response to a variety of physio‐ and pathological conditions dictated by an increase in workload of the myocardium, including ischemic cardiomyopathy,60, 61 hypertension,62 pressure overload,63 aging,20, 64 and heart failure 18, 65, 66. Thus, the enhanced beat‐to‐beat variability observed in diabetic myocytes may represent a feature shared with other diseased conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Our electrophysiological data support the possibility that similar alterations occur in the STZ‐hyperglycemic mouse model employed here. Importantly, reduction in the outward K + Kv currents and prolongation of AP duration in mammals appear to be a conserved response to a variety of physio‐ and pathological conditions dictated by an increase in workload of the myocardium, including ischemic cardiomyopathy,60, 61 hypertension,62 pressure overload,63 aging,20, 64 and heart failure 18, 65, 66. Thus, the enhanced beat‐to‐beat variability observed in diabetic myocytes may represent a feature shared with other diseased conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure was induced by rapid pacing from the RV following the protocols approved by Johns Hopkins University Animal Care and Use Committee [23]. Briefly, animals were intubated and anesthetized; blood oxygen saturation and expired CO 2 were kept within the physiological range throughout the procedure.…”
Section: Pacing-induced Heart Failure Protocolmentioning
confidence: 99%
“…Tissue samples from the hearts of four unoperated normal dogs were similarly obtained. We have previously shown that sham operated and unoperated controls exhibit similar mechanical, neurohumoral and electrophysiological phenotypes, thus to reduce cost and morbidity for the animals unoperated controls were used [9,11,23,24]. The canine pacing tachycardia model is characterized by systolic LV failure, preserved RV systolic function and no significant inflammation or fibrosis [24].…”
Section: Pacing-induced Heart Failure Protocolmentioning
confidence: 99%
“…a'i the lQ~a.J:d t:.ec:tifut:. CJl..t:.-rent, X KI , and the transient outward current, ITO' [5,6]; as well as a decrease in Na/K pump current [7]. It should be pointed out that the clinical relevance of the prolongation of action potential duration is still uncertain, since it has been shown to be present mostly at long, and often unphysiologic, cycle lengths.…”
Section: Electrophysiological Mechanismsmentioning
confidence: 99%